An efficient synthetic route for preparation of antimycobacterial wollamides and evaluation of their in vitro and in vivo efficacy. Issue 17 (15th September 2018) - Asfaw, Henok; Wetzlar, Thomas; Martinez-Martinez, Maria Santos; Imming, Peter
Graphical abstract: Highlights: An efficient and optimized synthetic route for the preparation of antimycobacterial wollamides is developed. The in vitro extracellular and intracellular antimycobacterial activities of the synthesized compounds were determined. For compounds with best in vitro antimycobacterial potency, in vivo proof of concept study was done. Abstract: A convenient solid phase peptide synthetic (SPPS) route is reported for the preparation of antimycobacterial wollamides. The method is based on on-resin head-to-tail cyclization and is fast, efficient and amenable to automation. The in vitro antimycobacterial activities of the newly synthesized wollamides were evaluated against M. tuberculosis H37Rv (Mtb H37Rv). To assess their drug-likeness, in vitro pharmacokinetic (ADME) profiling was also performed. For wollamides with potent extracellular potency, intracellular activities and in vivo efficacy were determined. The results disclose the potent antimycobacterial (MICMtb H37Rv = 1.1 µM) and suitable drug-like properties of wollamide A (4b ). Out of the synthesized wollamides, four compounds (4b –e ) exhibited potent intracellular activities against Mtb H37Rv infected human macrophages (IC50 = 0.2–1.3 µM). Results of in vivo blood exposure and efficacy assays for 4d and 4e are discussed.